Автоматизированная система определения глубины выгорания отработавшего ядерного топлива - Mokritskii, V. A.; Maslov, O. V.; Banzak, O. V. (PE "Politekhperiodika", Book and Journal Publishers, 2014)
The authors analyse their experience in application of semiconductor detectors and development of a breadboard model of the monitoring system for spent nuclear fuel (SNF). Such system should use CdZnTe-detectors in which one-charging gathering conditions are realized. The proposed technique of real time SNF control during reloading technological operations is based on the obtained research results. Methods for determining the burn up of spent nuclear fuel based on measuring the characteristics of intrinsic radiation are covered in many papers, but those methods do not usually take into account that the nuclear fuel used during the operation has varying degrees of initial enrichment, or a new kind of fuel may be used. Besides, the known methods often do not fit well into the existing technology of fuel loading operations and are not suitable for operational control. Nuclear fuel monitoring (including burn up determination) system in this research is based on the measurement of the spectrum of natural gamma-radiation of irradiated fuel assemblies (IFA), as from the point of view of minimizing the time spent, the measurement of IFA gamma spectra directly during fuel loading is optimal. It is the overload time that is regulated rather strictly, and burn up control operations should be coordinated with the schedule of the fuel loading. Therefore, the real time working capacity of the system should be chosen as the basic criterion when constructing the structure of such burn up control systems.